Examination of the Impact of Neighbourhood Green Spaces on the Rental Value of Selected Estates in Lagos (Island Axis) - Ndeche, C. B.; Agolua, C. K.; Sado, R. O. (International Journal of Real Estate, 2025)
Neighborhood green spaces play a crucial role in urban environments, significantly impacting the economic and social lives of residents. In Lagos, particularly the island axis, the scarcity of neighborhood green spaces has not been thoroughly examined in relation to its effect on rental values. Lagos is experiencing a significant shortage of green spaces due to rapid urbanization and population growth, resulting in the conversion of open areas into built-up environments. This study aims to examine the impact of neighbourhood green spaces on the rental value of selected estates in Lagos (Island axis). The objectives of this study are; to determine the effect of green spaces on the rental value of properties in the selected estates in Lagos Island; to evaluate residents’ perception of the importance of green spaces in their neighborhoods and to examine the potential economic benefits of green spaces to real estate owners, occupants and professionals in the study area. The population of study comprise of property owners, tenants within the selected estates, and estate surveyors and valuers managing the properties. The research will focus on a sample size of 335, with data collected primarily through questionnaire and direct interviews with collected data analyzed adopting descriptive statistics of frequency and percentages and accumulated percentages. Findings revealed that the presence of green spaces within walk-able distances attracts higher rental values with willingness of residence to pay to enjoy such benefits within the selected estates of the study area. However, these green areas should possess features that can enhance quality of life to warrant the rental difference. It was therefore recommended that urban planning policies be strictly implemented, increased investment in green infrastructure, better public-private partnership as well as community engagement in achieving a better green environment, strategic green space design among others.